PRINSIP-PRINSIP PENGEMBANGAN TRANSFORMASI PENDIDIKAN MADRASAH TSANAWIYAH DI MAKASSAR - Hanafi, Zain (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2019)
Developing a transformation of education characterized by Islam to be a necessary for educators and education personnel in Madrasah Tsanawiyah Indonesia. This research had revealed the principles used in developing the educational transformation of the Madrasah Tsanawiyah in Makassar which consists of personality education, interactional education, and educational technology. The questionnaire was used as one of the instruments to collect data from 68 samples and directed interviews were conducted to informants of school principles, staffs and teachers. the results of the study indicate that the principals of Madrasah had the same knowledge in developing the principles of educational transformation in Madrasah. Whereas, teachers and employees had a diversity of personality education, interaction skills and utilization of technology in developing the principles of educational transformation.